Redox doping method of high-performance tin-based perovskite solar cell

By introducing Eu2+ dopant into Sn perovskites, the concentration of Sn-I defect pairs is reduced by redox reaction in acid DMSO solvents, the stability and photoelectronic characteristics problems caused by Sn perovskite oxidation in Sn perovskite photovoltaic cells are solved, and Sn PSCs with high efficiency and high stability are achieved.

CN119730680APending Publication Date: 2025-03-28THE HONG KONG UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411330828.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-20
Filing Date
2024-09-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The oxidation of Sn4+ in Sn perovskite photovoltaic cells (PSCs) leads to the formation of Sn vacancy and Sn-I defect pairs, reducing structural stability and photoelectronic characteristics.

Method used

The optimized amount of europium diiodide (EuI2) was used as the metal ion dopant to introduce Eu2+ into an acid dimethyl sulfoxide (DMSO) solvent, and the concentration of Sn-I defect pair was reduced through redox reaction, and the doping effect of Eu2+ was verified by density functional theory (DFT) calculation and experimental method.

Benefits of technology

The power conversion efficiency (PCE) of Sn PSC is significantly improved to 13.66%, and the thermal stability of the perovskite lattice is enhanced, improving the photovoltaic performance and stability of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730680A_ABST
    Figure CN119730680A_ABST
Patent Text Reader

Abstract

The present application relates to a europium-doped tin-based perovskite for manufacturing an optoelectronic device exhibiting improved stability and high power conversion efficiency, and a perovskite precursor solution for preparing the europium-doped tin-based perovskite, wherein the europium-doped tin-based perovskite can be represented by Formula 1: (A +) (Sn < 2 + >) (X-) 3 m [(Eu < 2 + >) (Y-) 2] 1, wherein m is 0.001-0.05; x <-> in each case is independently F <->, Cl <->, Br <-> or I <->; y <-> in each case is independently F <->, Cl <->, Br <-> or I <->; and A + is Cs +, Rb +, CH3NH3 +, CH3CH2NH3 +, H (C = NH2) NH2 +, Me (C = NH2) NH2 +, or a mixture thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. Provisional Patent Application No. 63 / 585,224, filed on September 26, 2023, the entire contents of which are hereby incorporated by reference.

[0003] Statement regarding prior disclosure by inventor or co-inventor pursuant to 37 CFR 1.77(b)(6)

[0004] Part of the present invention has been disclosed in a paper published by Xue Ma et al. (Xue Ma et al., Europium redox doping to suppress Sn-I defect pairs in Sn perovskite photovoltaics, Device, Vol. 2, No. 6, 100294), which is available online on February 28, 2024. The paper is a disclosure initiated by the inventor of the grace period disclosed within one year before the filing date of this application, which is an exception to 35 USC § 102 (b) (1). The entire contents of the paper are hereby incorporated by reference. Technical Field

[0005] The present disclosure relates to europium-doped tin-based perovskites and optoelectronic devices including the europium-doped tin-based perovskites, and perovskite precursor solutions for preparing the europium-doped tin-based perovskites. Background Art

[0006] Metal halide perovskite solar cells (PSCs) are considered a pioneering photovoltaic technology due to their rapidly improving power conversion efficiency (PCE). However, high-performance PSCs are usually based on metal halide perovskites with lead (Pb) as the core metal cation, which is well known to be harmful to the environment and humans. Given the restrictions on the use of lead in commercial optoelectronic devices, its application in PSCs has been limited. To alleviate the Pb toxicity issue of PSCs while maintaining the ideal device performance, an important approach is to replace Pb cations with less toxic metal cations, especially tin (Sn) that exhibits a similar electronic configuration. Sn-PSCs have been shown to have high potential, with a maximum PCE of 14.81% reported. In addition, Sn perovskites with smaller band gaps are more ideal for absorbing sunlight compared to Pb perovskites. However, the Sn cations in perovskites can be converted from Sn to Sn. 2+ Easily oxidized to Sn 4+ , accompanied by Sn vacancies (V Sn ) to maintain the local electrical neutrality between the lattices. SnThe uncontrolled increase of Sn can severely degrade the structural stability and have a negative impact on the optoelectronic properties. Therefore, solving the Sn oxidation problem is of great significance for the pursuit of high stability and high efficiency Sn PSCs.

[0007] Current efforts are mainly focused on incorporating various functional molecules into Sn perovskite processing to improve the oxidation resistance of the resulting perovskite film via surface and interface passivation. However, barriers to charge extraction / transfer usually occur in the perovskite layer and its interface due to the insulating properties of the passivating molecules. Alternatively, metal ion doping is used to improve the performance and stability of Sn PSC devices. The general principle of metal ion doping is to introduce an appropriate amount of isovalent or heterovalent metal cations into the perovskite lattice to change the electronic and optical properties. Lithium (Li + ), sodium (Na + ), potassium (K + ) or rubidium (Rb + Interstitial doping of alkali metal cations such as ions has been widely used to suppress ion migration in perovskite materials, thereby enhancing the performance and stability of perovskite optoelectronic devices. However, these doping processes can distort the perovskite lattice, leading to lattice microstrain, which can affect the stability of the crystal. Therefore, the selection of appropriate ions is crucial to mitigate these side effects while maximally suppressing ion migration, thereby improving the performance and operational stability of PSCs.

[0008] Therefore, there is a need for improved Sn PSCs that address or overcome some of the above challenges. Summary of the invention

[0009] In this paper, we use an optimized amount of europium diiodide (EuI2) as a metal ion dopant, which can significantly suppress the Sn 4+ and undercoordinated I - We investigated the mechanism of this efficient method. We found that the Sn perovskite precursor solution in dimethyl sulfoxide (DMSO) solvent is acidic. In this acidic medium, Eu 2+ and Sn 4+ , iodine (I 0 ) are energetically more favorable. These reactions can reduce the concentration of Sn-I defect pairs in Sn perovskites. By combining density functional theory (DFT) calculations and experimental methods, it was confirmed that Eu 2+ The cations migrate into the perovskite lattice, which not only changes the local structure in the Sn-I framework, thereby reducing the energy barrier of the redox process, but also stabilizes the organic cation components, thereby improving the thermal stability of the Sn perovskite lattice. As a result, the Sn PSCs achieve a high PCE of up to 13.66% and an open circuit voltage (V OC ) is 0.72V, the short-circuit current density (JSC ) is 24.21 mA / cm 2 , the filling factor (FF) is 78.34%.

[0010] In a first aspect, the present invention provides a method comprising Sn 2+ and Eu 2+ of perovskite.

[0011] In certain embodiments, the perovskite further comprises a + , Rb + 、CH3NH3 + 、CH3CH2NH3 + 、NH2CH=NH2 + and NH2C(Me)=NH2 + One or more A + .

[0012] In certain embodiments, the perovskite further comprises NH2CH=NH2 + .

[0013] In certain embodiments, Eu 2+ and Sn 2+ They are present in the perovskite in a molar ratio of 0.01:99.99 to 5:95, respectively.

[0014] In certain embodiments, Eu 2+ and Sn 2+ They are present in the perovskite in a molar ratio of 0.5:99.5 to 2:98, respectively.

[0015] In certain embodiments, the perovskite further comprises NH2CH=NH2 + , and Eu 2+ and Sn 2+ They are present in the perovskite in a molar ratio of 0.5:99.5 to 2:98, respectively.

[0016] In certain embodiments, the perovskite has Formula 1:

[0017] (A + )(Sn 2+ )(X - )3·m[(Eu 2+ )(Y - )2] 1

[0019] Where m is 0.001-0.05;

[0020] X in each case - Independently F - , Cl - Br -or I - ;

[0021] Y in each case - Independently F - , Cl - Br - or I - ;as well as

[0022] A + It's Cs + , Rb + 、CH3NH3 + 、CH3CH2NH3 + 、H(C=NH2)NH2 + ,

[0023] Me(C=NH2)NH2 + or a mixture thereof.

[0024] In certain embodiments, A + It is H(C=NH2)NH2 + .

[0025] In certain embodiments, m is 0.005-0.02.

[0026] In certain embodiments, A + It is H(C=NH2)NH2 + , and m is about 0.01.

[0027] In certain embodiments, X - and Y - Each is 1.

[0028] In certain embodiments, the perovskite has Formula 2:

[0029] (H(C=NH2)NH2 + )(Sn 2+ )(I - )3·m[(Eu 2+ )(I - )2] 2

[0031] Where m is approximately 0.010101.

[0032] In a second aspect, the present invention provides a perovskite precursor solution comprising one or more tin salts, EuY2, AZ, optional tin powder, and a solvent, wherein the one or more tin salts are represented by the formula SnX2, A is Cs + , Rb + 、CH3NH3 + 、CH3CH2NH3 +、H(C=NH2)NH2 + 、Me(C=NH2)NH2 + or a mixture thereof, wherein X in each instance is independently F - , Cl - Br - ,I - or a mixture thereof, wherein Y in each case is independently F - , Cl - Br - ,I - or a mixture thereof, Z is F - , Cl - Br - or I - , and the solvent comprises dimethylformamide (DMF), dimethyl sulfoxide (DMSO) or a mixture thereof.

[0033] In certain embodiments, the one or more tin salts include SnF2, SnCl2, and SnI2.

[0034] In certain embodiments, AZ is H(C═NH 2 )NH 2 I.

[0035] In certain embodiments, Y is I - .

[0036] In certain embodiments, the perovskite precursor solution further comprises ethylenediamine dihydroiodide.

[0037] In certain embodiments, the perovskite precursor solution comprises tin powder, SnF2, SnCl2, SnI2, EuI2, H(C=NH2)NH2I, and DMSO.

[0038] In a third aspect, there is provided an electronic device comprising:

[0039] substrate layer;

[0040] A transparent conductive layer disposed on the surface of the substrate layer;

[0041] A hole transport layer disposed on the surface of the transparent conductive layer;

[0042] a perovskite layer comprising a perovskite described herein disposed on a surface of the hole transport layer;

[0043] an electron transport layer disposed on a surface of the perovskite functional layer; and

[0044] A metal electrode is disposed on the surface of the electron transport layer.

[0045] In certain embodiments, the electronic device has a power conversion efficiency (PCE) of 12-13.66%.

[0046] In certain embodiments, the perovskite has Formula 2:

[0047] (H(C=NH2)NH2 + )(Sn 2+ )(I - )3·m[(Eu 2+ )(I - )2] 2

[0049] Wherein m is about 0.010101, and the electronic device is more stable than the electronic device containing the perovskite of formula 3:

[0050] (H(C=NH2)NH2 + )(Sn 2+ )(I - )3

[0051] 3. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] The present invention is illustrated by the drawings and detailed description of various embodiments given below. The drawings should not be considered to limit the present invention to specific embodiments, but are used for explanation and understanding. The detailed description and drawings are only illustrative of the present invention and not limiting. The scope of the present invention is defined by the appended claims and their equivalents. The drawings are not drawn to scale. The above aspects and other attendant advantages of the present invention will be more easily understood by the detailed description in conjunction with the drawings.

[0054] Figure 1 . Crystal structure and grain distribution of perovskite films. (AC) Control, Sn 0 Sn 0 -Eu 2+ Depth-dependent grazing-incidence X-ray diffraction (GIXRD) patterns of FASnI3 perovskite films doped with Sn. (DF) Control, Sn. 0 Sn 0 -Eu 2+ SEM images of FASnI3 perovskite films doped with Sn. The scale bar represents 1 μm. (GI) are control, Sn 0 Sn 0 -Eu 2+ Grain size distribution histogram in the corresponding SEM images of the spiked samples.

[0055] Figure 2 .Eu 2+Characterization and calculation of doped perovskite films: crystal structure, electron localization, charge transfer, and redox properties. (A) Schematic diagram of a typical FASnI3 crystal structure, with Eu occupying the FA site (-2.3165 eV), Sn site (-3.2359 eV), and interstitial site (-6.735 eV) in sequence. 2+ Calculated formation energy (FE). (B)Eu 2+ The electron localization function (ELF) results of the doped perovskite film. The white dashed box represents the strong interaction between europium ions and iodine ions. (C) Undoped Eu 2+ and doped with Eu 2+ Time V I (D) Charge transfer calculated by Bader. (E) Standard reduction potential of acidic medium (E 0 ) The redox properties of various ions evaluated. (F) The E 0 With ΔG 0 Comparison of (ΔG 0 =-nFE 0 , where n is the number of electrons transferred in the reaction and F is the Faraday constant) (G) After exposure to air for 5 hours, Sn 0 -Eu 2+ High-resolution XPS spectra of Eu 3d-doped perovskite films.

[0056] Figure 3 . Characterization of surface properties. (A) Full XPS spectrum. (B, C and D) High-resolution XPS spectra: (B) Eu 3d, (C) I3d and (D) Sn 3d. (E and F) Fitted XPS peaks of Sn 3d: (E) Sn 0 Doped films and (F)Sn 0 -Eu 2+ (G) Control, Sn 0 Doped samples (blue) and Sn 0 -Eu 2+ Absorption spectra of the doped samples (orange-red). The inset shows the Tauc plot calculated from the absorption spectra. (H) C is deposited on the perovskite film. 60 Before and after, control (purple) on glass substrate, Sn 0 Doped perovskite film and Sn 0 -Eu 2+ PL spectra of perovskite films doped with C 60 The corresponding colors of the latter three perovskite films are light purple, light blue, and light orange-red.

[0057] Figure 4 .Calculation of the average electrostatic potential at different positions during the charge transfer process. (A) Control sample. (B) Sn0 -Eu 2+ The sample spiked with FA. Note that a, b, and c represent the electrostatic potential at different positions. (a) The line represents the electrostatic potential of electrons when they pass through the iodine skeleton in the presence of FA. (b) The line represents the electrostatic potential of electrons when they pass through the inorganic octahedral skeleton. (c) The rose dotted line represents the electrostatic potential of electrons when they pass through the Eu in the presence of FA. 2+ Electrostatic potential of electrons when iodine skeleton is incorporated. (C) The corresponding electron transition energy barriers for the two cases. F The values ​​are -3.5075eV (control sample) and -4.3441eV (Sn 0 -Eu 2+ spiked samples).

[0058] Figure 5 . Photovoltaic performance and stability. (A) Schematic diagram of energy band levels. (B) Control (purple), Sn 0 Doped PSC (blue) and Sn 0 -Eu 2+ JV curves of PSCs doped with Sn (red). (C) 0 -Eu 2+ JV curves and steady-state J SC and maximum power output (at 100mW cm -2 (D) Based on 15 devices of control, Sn 0 Doped PSCs and Sn 0 -Eu 2+ Statistical distribution of PCE of PSCs with Sn 0 Doped perovskite film and Sn 0 -Eu 2+ Normalized PL spectra of the doped perovskite films under different irradiation times.

[0059] Figure 6 . Recombination mechanism of the device. (A) Dark JV curve of PSC device. (B) Nyquist plot of PSC device. (C) Cross-sectional SEM image of FASnI3 device. (D, E, and F) JV characteristics of pure hole device with structure of ITO / PEDOT:PSS / perovskite / PTAA / Au for space charge limited current measurement.

[0060] Figure 7 .Optimize Eu 2+Concentration of doped samples (0, 0.5, 1, 2 mol %). (A) XRD patterns of perovskite films without EuI2 and with different amounts of EuI2. (B) Magnified XRD patterns of the 13.0-15.0° region of the corresponding figures. (C) Variation of (100) peak position and FWHM with doping concentration. (D) Williamson-Hall plot showing variation of relative strain (slope of fitted curve) with different EuI2 dopant concentrations. (E) Differential charge density calculated using a denser Γ-centered 12×16×16 k-point grid.

[0061] Figure 8 (A) UV-visible absorption spectrum. (B) Tauc plot calculated from the absorption spectrum. (C) Steady-state PL spectra of perovskite films without and with different amounts of EuI2.

[0062] Fig. 9 .(A) Control, (B) Sn 0 Doped films and (C)Sn 0 -Eu 2+ Air stability measurements of doped films: Unencapsulated perovskite films were placed in ambient air at 23 ± 3 °C and 25 ± 5% relative humidity for 0, 1, 2, 4, 6, 8, and 10 hours. The right figure shows the aging process. Sn 0 -Eu 2+ The films doped with Sn not only showed the strongest diffraction, but also maintained the diffraction intensity and film color for a long time. 0 The incorporated films showed relatively low peak intensity and poor stability. After storage for 64 hours, the peak intensity weakened rapidly.

[0063] Fig.10 Air stability measurements of precursor solutions (A, C, E correspond to fresh solutions; B, D, F correspond to aged solutions): Three bottles of precursor solutions were exposed to ambient air at a relative temperature of 23±3°C and a relative humidity of 25±5% for two months. The inset shows the corresponding photographs and SEM images of the solutions. The films prepared from the fresh solutions showed relatively strong diffraction intensity with uniform grains and clear grain boundaries. However, after two months, the films without Sn 0 -The solution without EuI2 changes from yellow to red, and the corresponding SEM image shows flocculence, indicating the presence of SnI4, which is confirmed by the XRD pattern. 0 and Sn 0 -Eu 2+ The sample showed higher FASnI3 diffraction intensity and maintained the original perovskite morphology, and the corresponding solution also maintained the yellow color.

[0064] Fig.11(A) XRD pattern of perovskite film on PEDOT:PSS coated substrate. (B) Magnified XRD pattern of the 13.5-29.0° region of the corresponding figure.

[0065] Fig.12 . Hydrogen potential (PH) test: We used pure DMSO, Sn 0 -FASnI3, Sn 0 -Eu 2+ -FASnI3 solution was dropped onto pH test paper and compared with the standard color card. Obviously, the pH value of FASnI3 perovskite precursor is less than 7, indicating that the solution is acidic, which is conducive to stabilizing Sn 2+ .

[0066] Fig.13 .Sn 0 -Eu 2+ Doped perovskite film (above) and Sn 0 High-resolution XPS spectra of (A) Sn 3d and (B) I 3d of the doped perovskite film (bottom), after exposure to air for 5 h.

[0067] Fig.14 .Sn 0 -Eu 2+ (A) SEM and (BF) elemental mapping of the doped FASnI3 perovskite film showing the distribution of (C) Sn, (D) Eu, (E) I, and (F) Cl elements; in addition, Sn 0 -Eu 2+ The energy dispersive X-ray spectroscopy (EDS) (G) and the corresponding elemental composition summary (H) of the doped FASnI3 perovskite films also confirmed the above elements.

[0068] Fig.15 .Depth-dependent XPS spectra of Eu 3d, the film was heated by argon (Ar + ) ions etched at depths of 0, 40, 80, and 120 nm. (A) Sn 0 Doped samples and (B) optimized 1 mol% Sn 0 -Eu 2+ Spiked samples.

[0069] Fig.16 .(AC)Sn 0 Doped FASnI3 film and (DF)Sn 0 -Eu 2+ Sn 3d in doped FASnI3 film 5 / 2 XPS Depth Profile XPS.

[0070] Fig.17 .(A, C)Sn 0Doped FASnI3 film and (B, D) Sn 0 -Eu 2+ Depth profile XPS of Sn 3d and I 3d in doped FASnI3 films (0, 40, 80, 120 nm using Ar ion etching).

[0071] Fig.18 Time-resolved PL spectra of Sn-perovskite films deposited on glass (A) and on PEDOT:PSS (B).

[0072] Fig.19 (A) Control, (B) Sn 0 Doped perovskite film and (C)Sn 0 -Eu 2+ Ultraviolet photoelectron spectroscopy (UPS) spectra of the doped perovskite films.

[0073] Fig. 20 .Based on a comparison of 15 devices (without Sn 0 - does not contain EuI2), Sn(Sn 0 doped) and Sn-Eu(Sn 0 -Eu 2+ (A)V of PSCs doped with OC 、(B)J SC Statistical distribution of (A) FF and (B) PCE. The upper and lower error bars in the box plots represent the highest and lowest values, respectively.

[0074] Fig.21 .Control and Sn 0 -Eu 2+ External quantum efficiency (EQE) of doped FASnI3 devices.

[0075] Fig. 22 (A) Control, (B) Sn deposited on PEDOT:PSS substrate 0 Doped perovskite film and (C)Sn 0 -Eu 2+ Cross-sectional SEM image of the doped perovskite film. Scale bar is 250 nm.

[0076] Fig.23 .Stability test: (A) The three samples were stored in a nitrogen atmosphere; (B) The three samples were exposed to air for measurement (relative humidity of 25±5%, temperature of 23±33°C).

[0077] Fig.24 .(AC) Control, (DF) Sn 0 Doped FASnI3 devices and (GI)Sn 0 -Eu 2+J-V curves of doped FASnI3 devices, which were exposed to AM 1.5G irradiation in a glove box to examine ion migration.

[0078] Fig.25 .Calculation of lattice parameters. When europium occupies the interstitial position, the lattice volume increases from 916.2642 Increased to 920.8437 This indicates that lattice expansion has occurred.

[0079] Fig.26 . Charge transfer according to Bader calculation.

[0080] Fig. 27 Electron transfer reactions in acidic FASnI3 precursors and the corresponding standard reduction potentials (E 0 ) and Gibbs free energy (ΔG 0 ). (ΔG 0 =-nFE 0 , where n is the number of electrons transferred in the reaction and F is the Faraday constant, which is 9.6485×10 4 C / mol).

[0081] Fig.28 .Based on glass substrate, undoped and Sn doped 0 -Eu 2+ The PL decay lifetime (τ1, τ2 and τ) of the perovskite film is shown in Figure 2. The reference formula is τ = τ1 × Rel1 (%) + τ2 × Rel2 (%).

[0082] Fig.29 .Depicts the structure of an exemplary optoelectronic device including the perovskite described herein according to certain embodiments, wherein the optoelectronic device includes: a substrate layer (101); a transparent conductive layer (102); a hole transport layer (103); a perovskite functional layer (104); an electron transport layer (105); and a metal electrode (106). DETAILED DESCRIPTION

[0083] definition

[0084] The following terms are used to describe the present invention. Unless specifically defined herein, the terms used to describe the present invention shall have the ordinary meanings understood by those of ordinary skill in the art.

[0085] Throughout the specification, unless the context requires otherwise, the word "comprise" or variations such as "comprises" or "comprising" should be understood to mean including the stated integer or group of integers but not excluding any other integer or group of integers. It should also be noted that in the present disclosure, especially in the claims and / or paragraphs, terms such as "comprises", "comprised", "comprising" may have the meanings ascribed to them in the U.S. Patent Law, for example, they may mean "includes", "included", "including", etc.; while terms such as "consisting mainly of" and "consisting mainly of..." have the meanings ascribed to them in the U.S. Patent Law, for example, they allow for elements not explicitly recited, but do not include elements existing in the prior art or elements that affect the basic characteristics or novel characteristics of the present invention.

[0086] In addition, throughout the specification and claims, unless the context requires otherwise, the word "include" or variations such as "includes" or "including", will be understood to imply the inclusion of a stated integer or group of integers but not the exclusion of any other integer or group of integers.

[0087] Unless otherwise specifically stated, the singular as used herein includes the plural (and vice versa). In addition, when the term "about" is used before a quantitative value, unless otherwise specifically stated, the present teachings also include the specific quantitative value itself. Unless otherwise stated or inferred, the term "about" as used herein refers to a deviation of ±10%, ±7%, ±5%, ±3%, ±1% or ±0% from the nominal value.

[0088] The present invention provides a Sn 2+ and Eu 2+ of perovskite.

[0089] Eu 2+ and Sn 2+The following molar ratios may be present in the perovskite: 0.01:99.99 to 10:90, 0.01:99.99 to 9:91, 0.01:99.99 to 8:92, 0.01:99.99 to 7:93, 0.01:99.99 to 6:94, 0.01:99.99 to 5:95, 0.01:99.99 to 4.5:95.5, 0.01:99.99 to 4:96, 0.01:99.99 to 3.5:96.5, 0.01:99.99 In certain embodiments, Eu 2O 2 is preferably selected from the group consisting of Eu 2O 2 and Eu 2O 2. In certain embodiments, Eu 2O 2 is preferably selected from the group consisting of Eu 2O 2 and Eu 2O 2. 2+ and Sn 2+ They are present in the perovskite in a molar ratio of about 1 to about 99, respectively.

[0090] Perovskite may also contain one or more + represents a cation, where A + Can be selected from Cs + , Rb + 、CH3NH3 + 、CH3CH2NH3 + 、NH2CH=NH2 + and NH2C(Me)=NH2 + In certain embodiments, A + is NH2C(Me)=NH2 + .

[0091] The perovskites described herein must be charge balanced. Therefore, the perovskites may also contain one or more counterions that balance the charge of the cations. Such counterions are not particularly limited and may be any anion. Example anions include, but are not limited to, F - , Cl - Br - ,I - and combinations thereof.

[0092] In certain embodiments, the perovskite may be represented by Formula 1:

[0093] (A + )(Sn 2+ )(X - )3·m[(Eu 2+ )(Y- )2] 1

[0095] Where m is 0.001-0.1;

[0096] X in each case - Independently F - , Cl - Br - or I - ;

[0097] Y in each case - Independently F - , Cl - Br - or I - ;as well as

[0098] A + It's Cs + , Rb + 、CH3NH3 + 、CH3CH2NH3 + 、H(C=NH2)NH2 + ,

[0099] Me(C=NH2)NH2 + or a mixture thereof.

[0100] The variable m represents the amount of europium doping in the perovskite described herein, and the ranges thereof may be 0.001-0.1, 0.001-0.09, 0.001-0.08, 0.001-0.07, 0.001-0.06, 0.001-0.05, 0.001-0.04, 0.001-0.03, 0.001-0.02, 0.001-0.04, 0.001-0.05, 0.001-0.06, 0.001-0.07, 0.001-0.06, 0.001-0.05, 0.001-0.06 ... .001-0.02, 0.005025-0.0204, 0.0101-0.0204, 0.0152-0.0204, 0.005025-0.0152, 0.00638-0.0142, 0.00753-0.0132, 0.0087-0.0121, 0.0091-0.011. In certain embodiments, m is about 0.010101. In certain embodiments, m corresponds to Eu 2+ With Sn 2+ The molar ratio is 0.5:99.6 to 1:99, 0.6:99.4 to 1.4:98.6, 0.7:99.3 to 1.3:98.7, 0.8:99.2 to 1.2:98.8 or 0.9:99.1 to 1.1:98.9.

[0101] In certain embodiments, A + It is H(C=NH2)NH2 +、Me(C=NH2)NH2 + or a mixture thereof. In certain embodiments, A + It is H(C=NH2)NH2 + .

[0102] In certain embodiments, X - and Y - Each is I.

[0103] In certain embodiments, the perovskite is represented by Formula 2:

[0104] (H(C=NH2)NH2 + )(Sn 2+ )(I - )3·m[(Eu 2+ )(I - )2] 2

[0106] Where m is approximately 0.010101.

[0107] The perovskite described herein can be prepared from a perovskite precursor solution, which comprises one or more tin salts, EuY2, AZ, optional tin powder, and a solvent, wherein the one or more tin salts are represented by the formula SnX2, A is Cs + , Rb + 、CH3NH3 + 、CH3CH2NH3 + 、H(C=NH2)NH2 + 、Me(C=NH2)NH2 + or a mixture thereof, wherein X in each instance is independently F - , Cl - Br - ,I - or a mixture thereof, wherein Y in each case is independently F - , Cl - Br - ,I - or a mixture thereof, Z is F - , Cl - Br - or I - , and the solvent comprises dimethylformamide (DMF), dimethyl sulfoxide (DMSO) or a mixture thereof.

[0108] The one or more tin salts may be present in the perovskite precursor solution at a concentration of 0.5-1.5M, 0.6-1.5M, 0.7-1.5M, 0.8-1.5M, 0.9-1.5M, 1.0-1.5M, 1.1-1.5M, 1.2-1.5M, 1.3-1.5M, 1.4-1.5M, 0.5-1.4M, 0.5-1.3M, 0.5-1.2M, 0.5-1.1M, 0.5-1.0M, 0.5-0.9M, 0.5-0.8M, 0.5-0.7M, 0.5-0.6M, 0.6-1.4M, 0.7-1.3M, 0.8-1.2M or 0.9-1.1M. SnI2 may be present in the perovskite precursor at a concentration range of 0.9-1.1 M, while SnCl2 is introduced at a concentration of 0.09 M-0.22 M. In certain embodiments, SnI2 and SnCl2 are present in the perovskite precursor solution at concentrations of about 0.9 M and about 0.093 M, respectively.

[0109] The Sn in the perovskite precursor solution can be suppressed by adding one or more of Sn powder and SnF2 to the perovskite precursor solution. 2+ Sn powder may be present in the perovskite precursor solution at the following concentrations: 0.04-0.8M, 0.1-0.8M, 0.2-0.8M, 0.3-0.8M, 0.4-0.8M, 0.5-0.8M, 0.6-0.8M, 0.7-0.8M, 0.04-0.7M, 0.04-0.6M, 0.04-0.5M, 0.04-0.4M, 0.04-0.3M, 0.04-0.2M, 0.04-0.1M, 0.2-0.7M, 0.3-0.6M or 0.4-0.5M. SnF2 may be present at a concentration of 0.09-0.11M. In certain embodiments, SnF2 is present in the perovskite precursor solution at a concentration of about 0.09M.

[0110] In certain embodiments, the perovskite precursor solution further comprises ethylenediamine dihydroiodide (EDADI).

[0111] The solvent can be any solvent that can at least partially dissolve one or more salts and AZ. In certain embodiments, the solvent is a polar aprotic solvent. Example solvents include, but are not limited to, dimethyl sulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAc), N-methyl-2-pyrrolidone (NMP), and mixtures thereof. In certain embodiments, the solvent comprises DMSO.

[0112] The perovskite described herein may be prepared by depositing a perovskite precursor solution on a substrate to form an unannealed perovskite film, and annealing the unannealed perovskite film to form the perovskite.

[0113] The perovskite precursor solution may be deposited on the substrate using any method known to those skilled in the art, including but not limited to spin coating, printing, screen printing, spray coating, painting, doctor bladder coating, slot die coating, and dip coating.

[0114] The unannealed perovskite film may be annealed at 40-150° C., 40-125° C., 40-100° C., 50-90° C., 60-80° C., or 65-75° C. In certain embodiments, the unannealed perovskite film is annealed at about 70° C.

[0115] The present disclosure also provides electronic devices comprising the perovskite described herein. Fig.29 The electronic device may include: a substrate layer (101); a transparent conductive layer (102) disposed on the surface of the substrate layer (101); a hole transport layer (103) disposed on the surface of the transparent conductive layer (102); a perovskite functional layer (104) comprising the perovskite described herein disposed on the surface of the hole transport layer (103); an electron transport layer (105) disposed on the surface of the perovskite functional layer (104); and a metal electrode (106) disposed on the surface of the electron transport layer (105).

[0116] The substrate (101) may comprise a flexible or rigid material having a light transmittance greater than 80% (at 550 nm). In certain embodiments, the substrate comprises: polymethyl methacrylate (PMMA), polycarbonate (PC), polystyrene (PS), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polydimethylsiloxane (PDMS), styrene-ethylene-butylene-styrene (SEBS), polyethylene terephthalate-1,4-cyclohexanedimethylene ester (ethyleneterephthalateco-1,4-cylclohexylenedimethylene terephthalate, PETG), acrylonitrile-butadiene-styrene copolymer (ABS), polypropylene (PP), polyamide (PA), acrylonitrile-styrene copolymer (AS) or a mixture thereof.

[0117] The transparent conductive layer (102) may include aluminum or indium doped zinc oxide, magnesium indium oxide, nickel tungsten oxide, gallium nitride, zinc selenide, zinc sulfide, zinc oxide (ZnO), tin dioxide (SnO2), lithium fluoride (LiF), zinc indium tin oxide (ZITO), indium tin oxide (ITO), aluminum zinc oxide (AZO), fluorine tin oxide (FTO), graphene, poly (3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), silver nanowires, copper nanowires or mixtures thereof.

[0118] The hole transport layer (103) may include SAM (self-assembled monolayer), PTAA (poly(triarylamine)), PEDOT:PSS, NiO x , Spiro-OMeTAD or a mixture thereof.

[0119] The perovskite functional layer (104) comprises a perovskite as described herein.

[0120] The electron transport layer (105) may include PC 61 BM, C60, SnO2 or a mixture thereof.

[0121] The metal electrode may include a resistivity less than 5×10 -7 Any metal having a resistance of Ω·m (at 25° C.). Example metal electrode metals include, but are not limited to, Ag, Cu, Au, Al, W, Fe, Pt, and mixtures thereof.

[0122] On the other hand, the present application provides a method for manufacturing an electronic device. In certain embodiments, a hole transport layer material is spin-coated on a transparent conductive layer (102) and annealed to form a hole transport layer (103). Then, a perovskite precursor solution is spin-coated on the hole transport layer (103) and annealed to form a perovskite functional layer (104). By vacuum thermal evaporation, an electron transport layer material and a metal electrode material are sequentially evaporated on the perovskite functional layer (104) to complete device preparation.

[0123] To synthesize the perovskite film samples, different concentrations (0, 0.5, 1.0, and 2.0 mol%) of europium dopant (EuI2) were added to FASnI3 (FA=NH2CH=NH2 + ) precursor solution, and then 0.1g / ml Sn metal powder was added as a solution oxidation resistor. Figure 7 A and Figure 7 B shows the X-ray diffraction (XRD) patterns of FASnI3 perovskite films with different amounts of EuI2. With the increase of doping concentration, the (100) and (200) diffraction peaks gradually shift to lower 2θ angles, indicating that Eu 2+ The lattice of the doped sample expands. These results indicate that Eu has entered the FASnI3 lattice, most likely into the interstitial space. In addition, the full width at half maximum (FWHM) of the XRD pattern shows that the crystallinity of the sample with 1 mol% EuI2 is the best due to the lowest FWHM value ( Figure 7 C). It is worth noting that the lattice structure of Sn-based perovskites usually exhibits strain and disorder due to the rapid crystallization process as well as hydrogen-bonding-induced octahedral tilting and local asymmetry. 2+The effect of lattice strain on FASnI3 perovskite was investigated by calculating the lattice microstrain (ε) from the Williamson-Hall plot of the XRD pattern. Figure 7 D) We found that the optimal doping amount of Eu 2+ This will lead to a decrease in the ε value, thereby reducing the lattice strain. This is attributed to the 2+ with FA + The interaction between them can offset the FA + The hydrogen bonding attraction between the octahedrons is Figure 7 This is confirmed by the DFT calculations in E.

[0124] The ultraviolet-visible (UV-vis) absorption spectra and steady-state photoluminescence (PL) spectra of the perovskite films were also used to examine the 2+ The optimal concentration ( Figure 8 ).according to Figure 8 The band gap obtained from the Tauc plot in B ( E g ) were calculated to be 1.380 eV (control), 1.381 eV (0.5 mol%), 1.386 eV (1.0 mol%), and 1.387 eV (2.0 mol%), respectively, indicating that the band gap gradually blue-shifts with increasing EuI2 dopant concentration, which is consistent with the results of XRD analysis. Similarly, the steady-state PL peak continues to blue-shift to shorter wavelengths. 2+ At a concentration of 1 mol%, the maximum intensity ( Figure 8 C). This significant increase in PL intensity is attributed to the reduction of microstrain and intragap traps in the EuI2-doped perovskite film, which in turn contributes to the reduction of non-radiative recombination. Based on all the above results, we believe that 1mol% is the optimal doping concentration and this concentration is adopted in the following studies.

[0125] As mentioned above, due to Sn 0 and Eu 2+ To achieve the synergistic effect, metal Sn powder was added to the Sn perovskite precursor solution. As confirmed by the literature, Sn powder can reduce the high concentration of Sn in the Sn perovskite precursor solution. 4+ Adding the optimal amount of EuI2 (1 mol%) is expected to further reduce Sn 4+ , inhibiting the neutral iodine (I 0 ) formation. To confirm this, we focused on comparing three samples (control: no addition of Sn powder and EuI2; Sn 0 Added: Add Sn powder but not EuI2; Sn 0 -Eu 2+ Doped: Sn powder and EuI2 are added simultaneously). Figure 1AC shows the depth-dependent grazing incidence X-ray diffraction (GIXRD) pattern, which reveals the perovskite structure from the top surface to the bulk region within the perovskite film. 0 The overall diffraction peak intensity of the sample doped with Sn 0 -Eu 2+ In addition, with the increase of grazing angle, the overall diffraction peak intensity of the control and Sn 0 The lattice constant of the doped samples did not change significantly (see Figure 1 When 1 mol% EuI2 was additionally introduced, the diffraction peak assigned to the (100) plane gradually shifted to a lower angle, indicating that Eu 2+ Entering the perovskite lattice ( Figure 1 C) More importantly, in Sn 0 -Eu 2+ A significant improvement in crystallization was observed near the surface of the doped samples. We believe that in addition to the Eu added to the lattice 2+ In addition to ions, there is also a small amount of Eu 2+ Distributed at the grain boundaries of the perovskite film, it may play a role in surface passivation, thus affecting the surface morphology.

[0126] Scanning electron microscopy (SEM) was used to characterize the surface morphology of different films. Figure 1 DF). The control film showed a relatively rough morphology with obvious pinholes and grain boundaries. Sn 0 The incorporated films show a relatively dense grain distribution, which may be attributed to the anti-oxidation property of Sn powder, which inhibits the formation of Sn vacancy defects. 0 -Eu 2+ The incorporated membrane exhibits a dense, uniform and pinhole-free morphology. Figure 1 The statistical measurement results in GI show that the average grain sizes of the three samples are 420nm (control), 410nm (Sn 0 doped) and 825nm(Sn 0 -Eu 2+ In Sn 0 -Eu 2+ The significantly improved morphology and enlarged grain size were observed in the films doped with Eu, which can be attributed to the incorporation of 2+ The ions change the surface energy, thus promoting a more directional crystal growth process, resulting in larger grain sizes and improved crystal quality.

[0127] The improvement of film morphology helps to protect the perovskite material from degradation caused by air humidity. Therefore, we exposed the prepared film samples to air for 10 h ( Fig. 9 In the control sample, a significantly faster lattice degradation was observed. 0 and EuI 2 , we can enhance the maintenance of the lattice and effectively prevent the lattice collapse. It is worth noting that when doping Sn 0 and Eu 2+ Can further enhance the membrane's anti-degradation ability. In addition, in order to evaluate the Eu 2+ The effects of the three perovskite solution samples were subjected to an aging experiment in air for two months ( Fig.10 ). 0 and Sn 0 -Eu 2+ Compared with the solution doped with Sn, the control solution showed a darker color, so the morphology of the obtained film was fibrous, which indicated that the Sn 4+ The concentration is higher, through Fig.10 XRD analysis in B can further prove that only Sn 0 Powder cannot effectively inhibit Sn 2+ Oxidation, as significant degradation was observed after two months of solution aging. Subsequent addition of EuI2 successfully obtained high-quality perovskite films with well-preserved crystal structures.

[0128] Given that Eu 2+ (109pm) or Eu 3+ (95pm) The radius of the ion is larger than that of Sn 2+ (93pm), but less than FA + (253 pm), the lattice expansion is likely due to Eu 2+ The ions occupy the Sn sites or interstitial sites in the FASnI3 lattice ( Fig.11 and Fig.25 ). Figure 2 A depicts the FASnI3 perovskite crystal structure and the insertion of Eu at the FA site (value -2.3165 eV), Sn site (-3.2959 eV), and interstitial site (-6.735 eV). 2+ The corresponding formation energy (FE). 2+ The lowest FE was observed when Eu was inserted into the interstitial position, which indicates that 2+ Mainly occupies the gap position. Figure 2 The electron localization function (ELF) analysis in B confirms that the electrons are transferred from Eu atoms to I atoms, which may hinder the iodine vacancy (V I ), it is known that iodine vacancies are prominent defects in tin-based perovskites. Figure 2 C, after introducing Eu 2+ After that, V I The FE of the defect increases from 3.582eV to 4.4983eV, resulting in I- The energy barrier for ion migration increases. Figure 7 Eu 2+ The charge density distribution shows that when Eu is doped at the interstitial position 2+ When Eu 2+ It can stabilize thermally unstable organic components, thereby enhancing the robustness of the structure and the stability of the lattice. In addition, we also analyzed the charge transfer between europium and tin through Bader charge distribution and found that europium has a greater electron loss and is more easily oxidized than tin ( Figure 2 D, for detailed parameters see Fig.26 ).

[0129] Sn 0 and Eu 2+ The redox properties of the ions can be characterized in alkaline or acidic environments by the solvent-dependent standard reduction potential (E 0 ) to evaluate. When dissolved in the neutral solvent dimethyl sulfoxide (DMSO), FASnI3 perovskite exhibits acidic behavior (see Fig.12 ), which promotes Sn 2+ Stability. Figure 2 In E, we outline four possible reactions of acidic precursors and Figure 2 F compares their E 0 Value (according to Fig. 27 Calculated). Figure 2 F, reaction 3 E 0 The highest value indicates that Eu 2+ Mainly acts as I 0 It is worth noting that Eu 2+ It showed stronger reducing ability than Sn powder, which indicated that it could effectively reduce Sn 4+ . Gibbs free energy change (ΔG 0 =nFE 0 , where n represents the number of electrons transferred in the reaction and F is the Faraday constant) as a criterion for evaluating the thermodynamic favorability of the reaction. 0 The value is negative, reactions 1, 2, and 3 occur spontaneously, while reaction 4 is determined to be thermodynamically unfavorable. 2+ Capable of creating suppression V Sn and V I The reducing environment formed.

[0130] In order to evaluate Eu 2+ To improve the oxidation resistance, we used aged Sn 0 and Sn 0 -Eu 2+ The perovskite films were prepared by using the doped precursors and then X-ray photoelectron spectroscopy (XPS) measurements were performed.2+ Tends to be more stable, through Fig.13 Sn in A 4+ Previous reports have shown that I 0 It is a byproduct of hydroiodic acid hydrolysis and a degradation product of SnI4. 0 Compared with the samples doped with Sn 0 -Eu 2+ The membranes spiked with I 0 ( Fig.13 B), which proves that Eu 2+ May also serve as I 0 The reducing agent. Figure 2 In G, Eu was observed at 1164.9 eV and 1135.2 eV, respectively. 3+ Peak, and Eu 2+ The peaks are detected at 1155.1eV and 1125.3eV respectively. 3+ The generation of Eu 2+ Sn 4+ and I 0 The redox reaction between 0 The value is negative.

[0131] We are Sn 0 -Eu 2+ Energy dispersive X-ray spectroscopy (EDS) mapping was performed on the doped samples ( Fig.14 ) to analyze the distribution of Eu. The spectrum shows a uniform surface distribution of Eu, accounting for 0.63% of the atomic mass. Figure 3 A shows the full XPS spectra of two fresh samples, where Figure 3 B is the enlarged view of Eu peak. The small peak that appears at the same time represents Eu 2+ and Eu 3+ , which may be attributed to the 4 + and I 0 The continuous redox reaction of the defect. Figure 3 C and 3D, doped with Eu 2+ After that, the E of I (0.40eV) and Sn (0.43eV) B This is also confirmed by the shift of the peaks to lower values. This shift can be attributed to the reduction of Sn and I oxidation states, which may be due to the 2+ The reduction process provides electrons. + ) performed depth-dependent XPS measurements on samples sputtered to different depths (0, 40, 80, and 120 nm) to evaluate the oxidation process within the perovskite layer. 2+It shows gradient doping, and the signal intensity decreases with increasing sputtering depth ( Fig.15 ). Figure 3 EF shows that in Sn 0 -Eu 2+ Sn on the surface of the doped samples 4+ The content is only 3.7%, which is significantly lower than Sn 0 This obvious difference persists with increasing sputtering depth, and it is observed that Sn 0 -Eu 2+ Sn doped samples 4+ Low content ( Fig.16 ). In addition, we noticed that the E of Sn and I in both samples increased with increasing sputtering depth. B The peaks shift to higher values ​​( Fig.17 ). Specifically, for Sn 0 For the samples doped with Sn, the XPS peaks of Sn 3d and I 3d shifted by 0.08 eV and 0.05 eV, respectively. 0 -Eu 2+ For the samples doped with Eu 2+ The introduction into the perovskite lattice changes the [SnI6] 4- The octahedral chemical environment leads to the doping of EuI 2 The XPS peak shifted significantly.

[0132] Compared with other samples, Sn 0 -Eu 2+ The doped films showed higher PL intensity ( Figure 3 H). This may be due to the fact that EuI2 enhances the crystallization of perovskite, thereby effectively passivating surface defects. 0 -Eu 2+ The doped films showed a blue shift to shorter wavelengths, which may be due to the removal of Sn 4+ In addition, time-resolved PL (TRPL) spectroscopy showed that Sn 0 -Eu 2+ The PL lifetime of the film doped with Sn is extended to 14.07 ns, which is higher than that of Sn 0 Doped membrane (7.09ns, Fig.18 A) is longer. After the electron transport layer is deposited, a significant PL quenching is observed ( Fig.18 A and Fig.28 ), which indicates that the addition of Eu 2+The ions may promote charge transfer at the interface. In general, various electrostatic potentials exist at different positions along the perovskite octahedral framework. Due to the insulating properties of organic molecules, the movement of electrons is restricted to the octahedral framework. In the presence of ammonium ions, the movement of electrons through the iodine framework changes its electrostatic potential due to steric hindrance. Theoretical calculations in this study show that after doping EuI2, the electrostatic potential of electrons in regions a, b, and c will change to varying degrees ( Figure 4 AB). We will Sn 0 -Eu 2+ The spiked samples (E F =-4.3441eV) and control (E F =-3.5075 eV) F ) are combined to determine the energy barrier for electron transfer. By changing the spatial arrangement of the Sn-I framework, Sn 0 -Eu 2+ The doping process significantly reduces the energy barrier for electrons to pass through the a region (-7.31 eV), b region (0.51 eV) and c region (-5.95 eV). Figure 4 C), thereby extending the carrier lifetime and facilitating charge collection. In addition, ultraviolet photoelectron spectroscopy (UPS) spectroscopy ( Fig.19 ) evaluated the electronic properties of FASnI3 perovskite films. Combined with the Tauc plot ( Figure 3 G) calculated band gap, we constructed the energy level diagram of the device ( Figure 5 A). Compared with the control sample (-4.82eV) and Sn 0 Compared with the sample doped with Sn (-5.11eV), 0 -Eu 2+ The valence band minimum (VBM) of the doped perovskite is -5.05 eV, which is closer to the VBM of PEDOT:PSS (-5.05 eV), which helps to reduce the energy loss during the charge transfer process. 0 -Eu 2+ E of spiked samples F The position is about 1.00 eV from VBM, while the control and Sn 0 The E of the doped device F The position is about 0.25eV and 0.89eV from VBM. The upward shift of E F It shows that severe oxidation leads to p-type doping in Eu 2+ can be suppressed afterwards.

[0133] We fabricated an inverted planar pin PSC and measured its current density-voltage (JV) curve ( Figure 5 B). The control device achieves the best PCE of 10.09%, JSC 21.97 mA / cm 2 , V OC is 0.62V, and FF is 74.10%. 0 After that, PCE increased to 10.69%, J SC 22.43 mA / cm 2 , V OC is 0.64V, and FF is 65.98%. 0 -Eu 2+ The device doped with J SC 24.21mA / cm 2 , V OC is 0.72V, and FF is 78.34%. The detailed photovoltaic parameters are shown in Table 1. More importantly, Sn 0 -Eu 2+ The JV hysteresis of the doped device is minimal ( Figure 5 C). At 100 mW cm -2 The Sn was measured at a bias voltage of 0.62 V under AM1.5G irradiation. 0 -Eu 2+ The maximum PCE output of the doped device was 2.3 % and maintained a stable efficiency output of about 13.5% without attenuation. Figure 5 D and Fig. 20 The corresponding box plots of photovoltaic parameters and hysteresis coefficient (HI) are shown. The improvement in PCE is mainly attributed to faster charge transfer and reduced defects, leading to J SC and V OC Increase. 0 -Eu 2+ The integrated J obtained by measuring the external quantum efficiency (EQE) of the doped device SC The values ​​are 21.64 mA cm -2 and 24.16 mA cm -2 , which is consistent with the J based on the JV results SC Very well matched. 0 -Eu 2+ J of the doped device SC The increase may be attributed to higher absorption in the 530-840 nm range ( Fig.21 ) and the thickness of the perovskite film increases ( Fig. 22 ). The substantial increase in film thickness is related to Sn 0 -Eu 2+ It should be noted that compared with the other two samples, the growth of larger grains in the Sn 0 -Eu 2+The samples doped with Eu show smaller JV hysteresis, which may be due to the fact that under AM 1.5G irradiation, the 2+ Inhibits I - The inhibition of hysteresis may be due to several factors: 1) Eu 2+ accumulate in the interstitial sites of the perovskite structure, which may hinder the I - Diffusion; 2) Eu 2+ Can interact with organic cations to stabilize the perovskite lattice; 3) Eu 2+ -Eu 3+ The distribution from the surface to the bulk is beneficial for passivating both surface and bulk defects.

[0134] Long-term stability is one of the important performance indicators for evaluating device performance. Sn stored in a nitrogen atmosphere 0 -Eu 2+ The doped devices showed good stability over 500 h ( Fig.23 A). During long-term exposure to air and AM 1.5G light irradiation ( Fig.23 B), Sn 0 -Eu 2+ The doped devices unexpectedly exhibited 80% retention of their initial efficiency, which may be attributed to the excellent photostability achieved through effective defect suppression and reduced ion migration pathways. To elucidate the effect of ion migration on the photostability of the perovskite film, PL measurements were performed at different irradiation durations ( Figure 5 E). Using 490 nm excitation light, we monitored the fluorescence signal and noticed that Sn 0 The peak of the doped perovskite film undergoes a significant red shift with the duration of irradiation, from 880.25nm to 890.51nm (a difference of 10.26nm) ( Figure 5 F). In contrast, Sn 0 -Eu 2+ The doped film showed a smaller shift, from 883.41 nm to 891.21 nm (7.80 nm shift) ( Figure 5 G). We believe that Eu 2+ with I 0 The reaction between ions, together with the lattice strain relief, inhibits iodine migration, thereby improving the photovoltaic stability of the device. Given that hysteresis is known to be due to ion migration under irradiation conditions, we monitored the JV curves of the three samples at different irradiation durations ( Fig.24 Devices without EuI2 exhibit severe hysteresis due to significant ion migration (from 4.3% to 13.8% for control devices, and from 1.3% to 2.5% for Sn devices). 0 doped devices, from 1.6% to 6.9%) Sn 0 -Eu2+ The doped samples showed only a small change in HI, from 1.1% to 1.3%, which indicates that the incorporation of Eu 2+ Effectively inhibits ion migration.

[0135] To evaluate the recombination of charge carriers in the device, we plotted the dark current to compare the shunt resistance ( Figure 6 A). Compared with other samples, Sn 0 -Eu 2+ The doped devices showed lower dark current (J0), indicating that charge carrier recombination was suppressed. In addition, electrochemical impedance measurements (EIS) were performed to evaluate their charge transfer ( Figure 6 B). The Nyquist plots of these devices all show a single semicircle, which corresponds to the resistance to charge recombination (R rec ) 0 -Eu 2+ The devices doped with rec , indicating that the Sn-I trap states are suppressed. To determine the trap density, we performed space charge limited current measurements using a device configuration of ITO / PEDOT:PSS / perovskite / PTAA / Au ( Figure 6 DF). Trap state density (N t ) is calculated using the following relationship: V TFL =qN t L 2 / 2εε0, where ε is the relative dielectric constant, ε0 is the vacuum dielectric constant, V TFL is the starting voltage of the trap filling limit region, q is the elementary charge, and L is the thickness of the perovskite film. The cross-sectional SEM image is shown in Figure 6 As shown in C. Fig. 22 As shown in Figure 2, under three different conditions, the thickness of the perovskite film is about 200nm, 220nm and 250nm respectively. 0 Doped devices and Sn 0 -Eu 2+ The V TFL The values ​​are inferred to be 1.85V, 0.36V and 0.3V. The corresponding N t The calculated values ​​are 2.42×10 16 cm -3 4.70×10 15 cm -3 and 3.92×10 15 cm -3 , which indicates that the trap density decreases significantly after doping with EuI2.

[0136] Table 1. Solar irradiance (100 mW cm) at AM 1.5G -2) condition, control, Sn 0 Doped devices and Sn 0 -Eu 2+ Photovoltaic parameters of the doped devices

[0137]

[0138] Note: The PCE reported in the table is the championship efficiency. FS refers to forward scan and RS refers to reverse scan.

[0139] in conclusion

[0140] Through combined experimental and DFT studies, we demonstrate that the optimal amount of Eu 2+ Ion doping into the FASnI3 perovskite lattice can relax the lattice strain, change the film morphology, and inhibit non-radiative recombination. More importantly, Eu 2+ Doping largely eliminates the Sn 2+ The Sn-I defect pairs generated by oxidation are attributed to the fact that under acidic precursor conditions, Eu 2+ Sn 4+ and I 0 Therefore, Eu 2+ The doped Sn PSC device can achieve a high efficiency of 13.66% with improved light and air stability. Our work provides a feasible approach to mitigate the challenging Sn-I defect problem faced by high-performance Sn perovskite photovoltaic devices.

[0141] experiment

[0142] Material

[0143] All chemicals were used directly after purchase without further treatment. FAI (99.999%), SnI2 (99.999%), SnF2 (99%), EDADI (99.9%), SnCl2 (99.999%), EuI2 (99.999%), sublimated fullerene-C60 (99.9%), and bathocuproine (BCP, 99%) were purchased from Sigma Aldrich, and poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS, Clevios VP AI 4083) was received from Heraeu. Ultra-dry dimethyl sulfoxide (DMSO) and ultra-dry chlorobenzene (CB) were purchased from Sigma Aldrich.

[0144] Device fabrication

[0145] The perovskite precursor solution was prepared by dissolving 336.3 mg SnI2, 14.1 mg SnF2, 154.77 mg FAI, 2.75 mg EDADI, 0.1 g / ml Sn powder, 17.64 mg SnCl2, 4.79 mg EuI2 in 1 ml DMSO solution and stirring the solution for 2 h at room temperature. The ITO glass substrate was cleaned by ultrasonic cleaning with detergent, DI water, acetone and isopropanol for 15 min, respectively. Then, the substrate was treated with UV-ozone for 20 min before spin coating PEDOT:PSS. The precursor solution was filtered through a 0.25 μm PTFE filter and spin coated on the PEDOT:PSS layer at 1000 rpm for 10 s and 5000 rpm for 50 s in a glove box. In the second step, 150 μL of chlorobenzene was added in situ onto the perovskite film after 40 s. Then, the perovskite film was annealed at 70 °C for 20 min. Finally, under high vacuum conditions, 100 nm of C 60 , 15nm BCP and 200nm Ag electrodes are sequentially evaporated on the perovskite.

[0146] Characterization

[0147] The X-ray diffractometer (Rigaku Smart Lab, Japan) was used with Cu Ka radiation (wavelength l = ) collected XRD results. SEM characterization and XPS spectra were measured by Hitachi Regulus 8100. NMR was measured on Bruker AVANCEIII600MHz. UV-visible absorption measurements were performed on a SHIMADZU UV-vis-NIR spectrometer (UV-1800). Steady-state and time-resolved photoluminescence spectra were measured using a Zolix OminiLuo-900 fluorescence spectrophotometer with an excitation wavelength of 490nm. The solar simulator (Saifan 7-IV) was used at 100mW / cm 2 The JV curves were measured under irradiation conditions using a Keithley 2450 source meter. The EQE was measured using a Zolix OminiLuo-900 fluorescence spectrophotometer. The EIS graphs were measured on a Zahner electrochemical workstation.

[0148] Calculation method

[0149] All first-principles calculations of the bulk system were performed using DFT in the plane wave / pseudopotential method implemented in the Vienna Ab-initio Simulation Package. The exchange correlations were described by the revised Perdew-Burke-Ernzerhof generalized gradient approximation (PBEsol), including dispersion correction of the total energy via Grimme's DFT-D3 scheme. In density functional theory, first-principles calculations were performed using the generalized gradient approximation (GGA) in the Perdew-Burke-Ernzerh exchange-correlation functional designed specifically for solids (PBEsol) by the Vienna Ab-initio Simulation Package (VASP). The crystal structure was optimized to a plane wave cutoff energy of 600 eV and a Γ-centered 3×4×4 k-point grid. All geometries were fully relaxed until the residual forces on each atom were less than The electronic density of states and the difference charge density were calculated using a denser Γ-centered 12×16×16 k-point grid. Some data post-processing in VASP calculations is handled by the VASPKIT code. Thus, the Sn vacancy formation energy can be obtained as follows:

[0150] E v =E tot (V)-E tot (Ideal)+μ

[0151] Among them, E v is the I vacancy formation energy, E tot (V) and E tot (Ideal) are the total energies of the defective supercell and the ideal supercell, respectively, and μ is the I chemical potential.

Claims

1. A perovskite comprising Sn 2+ and Eu 2+ .

2. The perovskite according to claim 1, further comprising one or more A selected from the following + :Cs + , Rb + 、CH3NH3 + 、CH3CH2NH3 + 、NH2CH=NH2 + and NH2C(Me)=NH2 + .

3. The perovskite according to claim 1, further comprising NH2CH=NH2 + .

4. The perovskite according to claim 1, wherein Eu 2+ and Sn 2+ They are present in the perovskite at a molar ratio of 0.01:99.99 to 5:95, respectively.

5. The perovskite according to claim 1, wherein Eu 2+ and Sn 2+ They are present in the perovskite at a molar ratio of 0.5:99.5 to 2:98, respectively.

6. The perovskite according to claim 1, further comprising NH2CH=NH2 + , and Eu 2+ and Sn 2+ They are present in the perovskite at a molar ratio of 0.5:99.5 to 2:98, respectively.

7. The perovskite of claim 1, wherein the perovskite has Formula 1: (A + )(Sn 2+ )(X - )3·m[(I 2+ )(Y - )2] 1 Where m is 0.001-0.05; X in each case - All are independently F - , Cl - Br - or I - ; Y in each case - All are independently F - , Cl - Br - or I - ;as well as A + It's Cs + , Rb + 、CH3NH3 + 、CH3CH2NH3 + 、H(C=NH2)NH2 + , Me(C=NH2)NH2 + or a mixture thereof.

8. The perovskite according to claim 7, wherein A + It is H(C=NH2)NH2 + .

9. The perovskite according to claim 7, wherein m is 0.005-0.

02.

10. The perovskite according to claim 7, wherein A + It is H(C=NH2)NH2 + , and m is about 0.

01.

11. The perovskite according to claim 10, wherein X - and Y - Each is I.

12. The perovskite of claim 1, wherein the perovskite has Formula 2: (H(C=NH2)NH2 + )(Sn 2+ )(I - )3·m[(Eu 2+ )(I - )2] 2 Where m is approximately 0.010101.

13. A perovskite precursor solution comprising one or more tin salts, EuY2, AZ, optional tin powder and a solvent, wherein the one or more tin salts are represented by the formula SnX2, A is Cs + , Rb + 、CH3NH3 + 、CH3CH2NH3 + 、H(C=NH2)NH2 + 、Me(C=NH2)NH2 + or a mixture thereof, wherein X in each case is independently F - , Cl - Br - ,I - or a mixture thereof, wherein Y in each case is independently F - , Cl - Br - ,I - or a mixture thereof, Z is F - , Cl - Br - or I - , and the solvent comprises dimethylformamide (DMF), dimethyl sulfoxide (DMSO) or a mixture thereof.

14. The perovskite precursor solution of claim 13, wherein the one or more tin salts include SnF2, SnCl2, and SnI2.

15. The perovskite precursor solution according to claim 13, wherein AZ is H(C=NH2)NH2I.

16. The perovskite precursor solution according to claim 13, wherein Y is 1 - .

17. The perovskite precursor solution according to claim 13, further comprising ethylenediamine dihydroiodide.

18. The perovskite precursor solution according to claim 13, wherein the perovskite precursor solution comprises tin powder, SnF2, SnCl2, SnI2, EuI2, H(C=NH2)NH2I and DMSO.

19. An electronic device comprising: substrate layer; A transparent conductive layer disposed on the surface of the substrate layer; A hole transport layer disposed on the surface of the transparent conductive layer; A perovskite layer comprising the perovskite of claim 1 disposed on the surface of the hole transport layer; An electron transport layer disposed on the surface of the perovskite functional layer; as well as A metal electrode is disposed on the surface of the electron transport layer.

20. The electronic device of claim 19, wherein the power conversion efficiency (PCE) of the electronic device is 12-13.66%.

21. The electronic device of claim 19, wherein the perovskite has Formula 2: (H(C=NH2)NH2 + )(Sn 2+ )(I - )3·m[(Eu 2+ )(I - )2] 2 wherein m is about 0.010101, and the electronic device is more stable than an electronic device comprising a perovskite of Formula 3: (H(C=NH2)NH2 + )(Sn 2+ )(I - )3 3。